2017
DOI: 10.1177/1941738117734149
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Drive Youth Specialization

Abstract: Background:Specialization in young athletes has been linked to overuse injuries, burnout, and decreased satisfaction. Despite continued opposition from the medical community, epidemiological studies suggest the frequency is increasing.Hypothesis:Extrinsic pressures in addition to individual aspirations drive this national trend in sports specialization.Study Design:Descriptive epidemiology study.Level of Evidence:Level 3.Methods:A novel instrument assessing the driving factors behind youth specialization was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 23 publications
2
39
1
Order By: Relevance
“…Regardless of whether they were classified as moderately or highly specialized, the gymnasts in our sample had high training volumes that exceeded recommendations from several medical organizations. All of the moderately and highly specialized gymnasts reported that they trained more than 8 months of the year, which was higher than the 60% described by youth athletes participating in other sports, 18 perhaps demonstrating the early specialization often required in gymnastics. The American Academy of Pediatrics recommended that regardless of sport, youth athletes should take at least 3 months off from their primary sport to allow for physical and psychological recovery; however, they can still be involved in other physical activities.…”
Section: Discussionmentioning
confidence: 81%
“…Regardless of whether they were classified as moderately or highly specialized, the gymnasts in our sample had high training volumes that exceeded recommendations from several medical organizations. All of the moderately and highly specialized gymnasts reported that they trained more than 8 months of the year, which was higher than the 60% described by youth athletes participating in other sports, 18 perhaps demonstrating the early specialization often required in gymnastics. The American Academy of Pediatrics recommended that regardless of sport, youth athletes should take at least 3 months off from their primary sport to allow for physical and psychological recovery; however, they can still be involved in other physical activities.…”
Section: Discussionmentioning
confidence: 81%
“…13 The relative risk of injury was significantly higher in ultracompetitive regions known to produce high-level collegiate prospects. 18,19 As health care providers become increasingly aware of the epidemic of elbow injuries in young baseball players, accurate distribution of preventative information to the baseball community is necessary. This begins with expanding the role of clinicians from a focus on treatment to a focus on preventative education.…”
mentioning
confidence: 99%
“…57,113 Coaches also appear to be an additional source of pressure, especially in the context of persuading an athlete to cease playing other sports. 13 However, not all coaches may share this perspective. Recent research showed that approximately 67% (n=170) of youth sport coaches believed that yearround participation in a single sport was either "very" or "extremely" likely to increase an athlete's injury risk.…”
Section: Chapter V: Discussionmentioning
confidence: 99%
“…However, investigations examining the influences leading an athlete to specialize have only begun to reach the surface. Padaki et al 13 identified two external pressures that are prevalent among specialized athletes: parents and coaches. Specialized athletes were more likely to report being told to not participate in other sports by their coaches and parents.…”
Section: Chapter I: Introductionmentioning
confidence: 99%
See 1 more Smart Citation